Developing a Scale to Evaluate the Performance of Football Coaches from the Players’ Perspective - Saher Mohammed Hameed; Imad Saad Allah Khamis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Since the coach is the absolute core element in the process of success in training and the sport-specific goals, this study has been conducted in order to develop a scale to assess the football coaches based on the perspectives of the players. Given the nature of the study, the researcher used the descriptive method significantly the survey approach. Football players were used as the study population. The sampling method was non-random and involved a total of 80 players, 20 in the pilot and 60 in the main study. It was designed based on the scientific rules of scale-building. It had various dimensions associated with some aspects of the coach's job. Content validity was ensured and test–retest method was employed to establish reliability. Faialdani and Aleem 2020. The objective of this study was to develop the scale for assessing the performance of football coaches and to determine its validity and reliability as well. Methods: The scale was handed out to886 football coaches who have either bachelor graduation degree or higher from 16 provinces in Iran, covering the entire country.